„Nieszczęsny dar” ateizmu. Szkic do perspektywy dialogu – wyzwania i trudności - Jerzy Tupikowski (Wrocławski Przegląd Teologiczny)
This article explores the complexity of the phenomenon of atheism in the horizon of human freedom. Starting from as it seems the right diagnosis of the problem presented by Rev. Prof. J. Tischner, the paper shows a prospect of the dialogue at the crossroads of fundamental contemporary religious and ideological choices and attitudes. They are represented, as it is expressed by L. Kołakowski, by the three leading “protagonists”: “the mystic”, “the skeptic” and “the nihilist”. The dialogue between reason and faith conducted in the field of skeptic’s sharp arguments and in the light of testimony given by the mystic, though difficult, is possible. In fact, religious faith demands “a speech about God”, while doubt, provided it is an authentic pursuit, namely a search for truth, is actually an initial opening up to God being the Truth.